Biomass, Seed and Energy Yield of Cynara cardunculus L. as Affected by Environment and Season - Anita Ierna; Orazio Sortino; Giovanni Mauromicale (Agronomy, 2020)
Cynara cardunculus is a perennial plant that adapts well to Mediterranean climate conditions. The possibility of cultivating C. cardunculus with low or zero input and in low productivity or marginal lands makes it one of the most promising crops for bioenergy production in the Mediterranean areas. The objective of the research was to study the effects of two marginal and contrasting southern Italian environments (plain, 42 m a.s.l. and hilly area, 419 m a.s.l.) during a three-year period on biomass, seed, energy yield, and oil composition of two genotypes of C. cardunculus (cultivated cardoon and wild cardoon). When compared to the plain, plants that were grown in the hills gave higher biomass yield (10.9 vs. 9.7 t DM ha−1 year−1), higher seed yield (0.46 vs. 0.44 t DM ha−1 year−1) and, consequently, higher total energy yield (190 vs. 172 GJ ha−1 year−1), attributable to higher average annual rainfall (680 vs. 565 mm year−1). The season, although only evaluated for three years (short cycle), showed a different effect based on the genotype, highlighting a greater over-time production constancy of wild cardoon (though less yielding) as compared to cultivated cardoon. Oil yield and composition were only slightly affected by environment and genotype. Overall, the results of this research suggest using C. cardunculus in marginal hilly areas, where, in addition to the production of bioenergy, it may represent a good chance to fight erosion and improve soil fertility, without competing with food crops.